The Estimation of Glomerular Filtration Rate (GFR) for Renal Split Function with 99mTc-DTPA - Hossain, Alamgir; Islam, Bedarul; Ckaki, Chanchal K.; Shaha, Samirun Kumar; Chowdhury, Shariful I. (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2015)
Introduction: To study the variation of kidney counts, uptake and Glomerular filtration rate with renal split function, 27 patient’s renogram data were taken. Therefore, toinvestigate of glomerular filtration rate (GFR) for renal split function with 99mTc-DTPA.Procedures: The injected dose was calibrated by the dose calibrator. About 3mCi 99mTc with DTPA are taken into the syringe. With the help of gamma camera,the pre syringe counts (in Kcpm units) and post syringe counts (Kcpm units) are measured. From the value ofpre syringe counts and post syringe counts,the net injected counts are measured. Then the patient is placed on the imaging beds and the detector of the gamma camera is placed on the suitable position. The gamma rays are counted by the detector of the gamma camera,in which emits from the kidney of the patients andthe display unit shows the curve time versus counts per minute, Renal split function, uptake, Glomerular filtraration rate, kidney depth, and time of maximum counts for left and right kidney respectively by automated software (Easy soft-Semence signature series) programm. Results: The renal split function were investigated in the range of (89.99~22.4) %for left kidney and also (99.6~6.377) %for right kidney. It was found that the range of uptake (%), (8.019~2.2236) %for left kidney and (7.765~1.19) %for right kidney. The GFR were found in the range of (72.4~20.4) ml/min for left kidney and also (70.9~3.937) for right kidney.Conclusion: The GFR was linear relationship with renal split functions but linearly decreased with patient’s age. For majority patients, the calculated value of GFR were (20-30) (ml/min) and (40-50) (ml/min) in left and right kidney respectively. Therefore, majority patient wasaffected in cardiovascular disease (CVD)